Building inclusive PA classrooms: The Diversity Inclusion Model. Issue 1 (March 2021) - Evans, Michelle D; Knepper, Hillary J
Normative management behaviors have resulted in the patterns of today—a lack of equity in leadership positions and policies that are less favorable toward women. Meanwhile, public service values, such as respect, equity, diversity, and inclusiveness, are central foci among the professional standards and norms within the public administration field, its academic discipline and related curricula. Consequently, public administration educational programs are uniquely situated to espouse these values in their core curricula, as well as enact and reinforce them through inclusive pedagogical practices. This paper has two aims. First, to introduce the Diversity Inclusion Model, which provides a framework for examining diversity and inclusion in course design and syllabi to identify areas of improvement. Second, to apply the Diversity Inclusion Model to gender equity and inclusion to develop more gender-inclusive, acculturated learning experiences that reinforce gender equity in the classroom. This may subsequently inform the practice of public administration to re-shape professional norms and create better gender equity.